Mesothelioma Risk among Construction Workers According to Job Title: Data from the Italian Mesothelioma Register - Vimercati, Luigi; Cavone, Domenica; De Maria, Luigi; Caputi, Antonio; Pentimone, Floriana; Sponselli, Stefania; Delvecchio, Giuseppe; Chellini, Elisabetta; Binazzi, Alessandra; Di Marzio, Davide; Mensi, Carolina; Consonni, Dario; et al. (La Medicina del Lavoro, 2023)
Background: An increased risk of mesothelioma has been reported in various countries for construction workers. The Italian National Mesothelioma Registry, from 1993 to 2018, reported exposure exclusively in the construction sector in 2310 cases. We describe the characteristics of these cases according to job title. Methods: We converted into 18 groups the original jobs (N=338) as reported by ISTAT codes (‘ATECO 91’). The exposure level was attributed at certain, probable and possible in accordance with the qualitative classification of exposure as reported in the Registry guidelines. Descriptive analysis by jobs highlights the total number of subjects for each single job and certain exposure, in descending order, insulator, plumbing, carpenter, mechanic, bricklayer, electrician, machine operator, plasterer, building contractor, painter and labourer. Results: The cases grow for plumbing in the incidence periods 1993-2018, while, as expected, it decreases for insulator. Within each period considered the most numerous cases are always among bricklayers and labourers, these data confirm the prevalence of non-specialised "interchangeable" jobs in Italian construction sector in the past. Conclusions: Despite the 1992 ban, the construction sector still presents an occupational health prevention challenge, circumstances of exposure to asbestos may still occur due to incomplete compliance with prevention and protection measures.